2013
DOI: 10.1371/journal.pone.0069701
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Lymphatic System in Breast Cancer Patients with Magnetic Resonance Lymphangiography

Abstract: ObjectiveTo investigate the feasibility of gadolinium (Gd) contrast-enhanced magnetic resonance lymphangiography (MRL) in breast cancer patients within a typical clinical setting, and to establish a Gd-MRL protocol and identify potential MRL biomarkers for differentiating metastatic from non-metastatic lymph nodes.Materials and Methods32 patients with unilateral breast cancer were enrolled and divided into 4 groups of 8 patients. Groups I, II, and III received 1.0, 0.5, and 0.3 ml of intradermal contrast; grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
1
12
0
3
Order By: Relevance
“…Here, we demonstrated that breast tumors lacking VEGF-D expression do not exhibit a defect in primary tumor or lymph nodes lymphangiogenesis, but have a reduced amount of dilated lymphatic vessels associated with an inhibition of metastasis. Our findings suggested that this process is restricted to breast cancer, in agreement with previous studies showing a correlation between metastases and dilated lymphatic vessels in breast cancer patients (40).…”
Section: Discussionsupporting
confidence: 93%
“…Here, we demonstrated that breast tumors lacking VEGF-D expression do not exhibit a defect in primary tumor or lymph nodes lymphangiogenesis, but have a reduced amount of dilated lymphatic vessels associated with an inhibition of metastasis. Our findings suggested that this process is restricted to breast cancer, in agreement with previous studies showing a correlation between metastases and dilated lymphatic vessels in breast cancer patients (40).…”
Section: Discussionsupporting
confidence: 93%
“…Meme kanseri hastalarında ALN tutulumu hastalığın prognozunu olumsuz yönde etkilediği gibi klinik ve cerrahi yaklaşımı belirleyen önemli bir faktördür. Malign meme tümörünün aksiller lenf nodlarına yayılımı, 10 yıllık rekürrens oranını %20-30'dan %70'lere çıkarmaktadır [2]. Bu nedenle, yeni tanı almış tüm meme kanseri hastalarında ALN tutulumunun değerlendirilmesi çok önemli bir zorunluluktur.…”
Section: Derlemeunclassified
“…Level-2 veya orta aksiller lenf nodları pektoralis minör kasının arkasında yer alır ve patolojik boyut ya da ekojenitede olmadığı takdirde kolayca saptanamayabilir. Level 3, yani apikal aksiller lenf nodları pektoralis minör kasının medialinde infraklaviküler bölgede yer alır [2,5]. Rotter (interpektoral) nodları, level-2 orta aksiller lenf nodlarının pektoralis majör ve minör kasları arasında yer alan bir bölümüdür [5].…”
Section: Meme Lenfatik Sistem Anatomisi Ve Lenf Nodu Histolojisiunclassified
“…The technique is relatively non-invasive and can be used to identify anatomic and physiological abnormalities associated with lymphatic dysfunction in order to determine further treatment strategies (Lohrmann et al, 2009). MRL has shown promise in imaging the lymphatic system in multiple pathologies including breast cancer (Lu et al, 2013), lymphedema (Lohrmann et al, 2007; Rane et al, 2013) and diffuse lymphangiomatosis (Lohrmann et al, 2011). Imaging agents with better sensitivity and specificity are under development (McDermott et al, 2013) and will improve the ability of MRL to identify pathologies in the lymphatic system.…”
Section: Imaging the Lymphatic System In The Clinic For Assessment Ofmentioning
confidence: 99%